2023
DOI: 10.3389/fmars.2023.1052166
|View full text |Cite
|
Sign up to set email alerts
|

Global ocean colour trends in biogeochemical provinces

Abstract: Satellite-derived ocean colour data provide continuous, daily measurements of global waters and are an essential tool for monitoring these waters in a changing climate. Merging observations from different satellite sensors is necessary for long-term and continuous climate research because the lifetime of these sensors is limited. A key issue in deriving long-term trends from merged ocean colour data is the inconsistency between the spatiotemporal coverage of the different sensor datasets that can lead to spuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 89 publications
(131 reference statements)
0
0
0
Order By: Relevance
“…These four products show very similar patterns as they are all partially based on the NASA R2018.0 and ESA reprocessing for their respective sensors, unlike Globcolour-GSM which derives Schl thanks to a specific semi-analytical ocean color model (Maritorena et al, 2002). Considering now the OC-CCI product which is widely used in the ocean color community (e.g., Fowler et al, 2023;van Oostende et al, 2023), a decreasing trend can be observed in the northern and equatorial Pacific Ocean, along the Pacific Intertropical Convergence Zone (ITCZ), the tropical Indian and northern Atlantic Oceans (Figure 1b). However, a significant positive trend of Schl appears in the northern hemisphere for higher latitudes than 40°N and in the Southern Ocean generally south of the Subtropical Front (Graham & Boer, 2013), as well as in the south-eastern Pacific.…”
Section: Resultsmentioning
confidence: 91%
“…These four products show very similar patterns as they are all partially based on the NASA R2018.0 and ESA reprocessing for their respective sensors, unlike Globcolour-GSM which derives Schl thanks to a specific semi-analytical ocean color model (Maritorena et al, 2002). Considering now the OC-CCI product which is widely used in the ocean color community (e.g., Fowler et al, 2023;van Oostende et al, 2023), a decreasing trend can be observed in the northern and equatorial Pacific Ocean, along the Pacific Intertropical Convergence Zone (ITCZ), the tropical Indian and northern Atlantic Oceans (Figure 1b). However, a significant positive trend of Schl appears in the northern hemisphere for higher latitudes than 40°N and in the Southern Ocean generally south of the Subtropical Front (Graham & Boer, 2013), as well as in the south-eastern Pacific.…”
Section: Resultsmentioning
confidence: 91%